Childhood trauma is associated with perceived stress and hair cortisol levels characterized by the BDNF Val66Met genotype and sex - Zhenxu Li; Zhenxu Li; Se Jun Koo; Hye Yoon Park; Jee Eun Min; Jung Tak Park; Jung Tak Park; Eun Lee; Eun Lee; Suk Kyoon An; Suk Kyoon An (Frontiers in Psychiatry)
IntroductionChildhood trauma increases the risk of mental disorders by affecting both psychological and physiological stress responses in adulthood, including perceived stress and long-term hypothalamic-pituitary-adrenal (HPA) axis activity. The mechanisms underlying these effects may involve gene-environment (G × E) interactions, with the brain-derived neurotrophic factor (BDNF) gene Val66Met polymorphism and sex playing important roles. This study aims to investigate how childhood trauma influences stress responses, considering the BDNF Val66Met polymorphism and sex differences.MethodsSecondary data from 190 healthy young adults (96 female) were analyzed. Childhood trauma and perceived stress were assessed using the Childhood Trauma Questionnaire (CTQ) and the Perceived Stress Scale (PSS), respectively, and hair cortisol concentration (HCC) was assessed as a measure of long-term cortisol levels. Participants were genotyped for the BDNF Val66Met polymorphism and stratified as Val/Val or Met carriers. Hierarchical linear regression models were used to examine the interactions between CTQ scores, BDNF Val66Met genotype, and sex to assess their effects on PSS scores and HCC. Additional analyses included separate linear regression models of the CTQ scores for HCC in Val/Val and Met carriers according to sex.ResultsHigher CTQ scores were positively associated with PSS scores in the entire sample (B= 0.124, p = 0.002). No significant main effects of CTQ scores, BDNF Val66Met genotype, or sex on HCC were observed. However, a significant three-way interaction between CTQ scores, BDNF Val66Met, and sex on HCC was observed, with a positive association between HCC and childhood trauma observed exclusively in female Val/Val carriers (B= 0.019, p=0.034).ConclusionThese results demonstrated that childhood trauma elevates perceived stress across all participants and increases HCC levels, specifically in female Val/Val carriers.